The direct cost burden of 13 years of disabling workplace injuries in the U.S. (1998–2010): Findings from the Liberty Mutual Workplace Safety Index. (December 2015) - Marucci-Wellman, Helen R.; Courtney, Theodore K.; Corns, Helen L.; Sorock, Gary S.; Webster, Barbara S.; Wasiak, Radoslaw; Noy, Y. Ian; Matz, Simon; Leamon, Tom B.
Abstract: Introduction : Although occupational injuries are among the leading causes of death and disability around the world, the burden due to occupational injuries has historically been under-recognized, obscuring the need to address a major public health problem. Methods : We established the Liberty Mutual Workplace Safety Index (LMWSI) to provide a reliable annual metric of the leading causes of the most serious workplace injuries in the United States based on direct workers compensation (WC) costs. Results : More than 600 billion in direct WC costs were spent on the most disabling compensable non-fatal injuries and illnesses in the United States from 1998 to 2010. The burden in 2010 remained similar to the burden in 1998 in real terms. The categories of overexertion (13.6B, 2010) and fall on same level (8.6B, 2010) were consistently ranked 1st and 2nd. Practical application : The LMWSI was created to establish the relative burdens of events leading to work-related injury so they could be better recognized and prioritized. Such a ranking might be used to develop research goals and interventions to reduce the burden of workplace injury in the United States. Highlights: The LMWSI is an annual metric based on workers compensation (WC) costs of the most disabling non-fatal workplace injuries. Between 1998 and 2010 the LMWSI grew by 38%, from 37.1 billion to 51.1 billion in nominal terms. After adjusting for inflation, the burden in 2010 was similar in real-terms to the burden in 1998. Even after adjusting for inflation, injuries for fall on same level category, cost America 2 billion more in 2010 than 1998. The burden of overexertion injuries still far outweighs any other cause